The Effect of Training and Career Development on Employee Performance through Employee Physical Activity at PT. Laris Cargo Medan - Fanni Karniawan Hulu; Nurhasanah Sihotang; Raymond Fransiscus (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to analyze the effect of training and career development on employee performance through the mediation of employee physical activity at PT. Laris Cargo Medan through a case study with a quantitative design. The sample consisted of 150 employees (response rate 92%) selected using stratified random sampling from a total population of 163 employees. Data were collected using a validated 5-scale Likert questionnaire (Cronbach α=0.87-0.94) measuring the variables of training and career development (X), employee physical activity (M), and employee performance (Y). The analysis was conducted using Structural Equation Modeling (SEM) with AMOS 26.0 and the Sobel test for mediation. The results showed that training and career development had a significant positive effect on employee physical activity (β=0.62, p<0.001, R²=0.385) and employee performance (β=0.41, p<0.001, R²=0.168). Employee physical activity partially mediated the relationship (β=0.29, p=0.002, z=3.45). The structural model explained 58.4% of the variance in employee performance. The study concluded that training and career development improve employee performance directly and indirectly through employee physical activity at PT. Laris Cargo Medan. This finding demonstrates the importance of integrating physical health programs into human resource development strategies to optimize the productivity of logistics companies.